2018
DOI: 10.1111/ijlh.12937
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of light transmission aggregometry and multiple electrode aggregometry for the evaluation of patients with mucocutaneous bleeding

Abstract: Introduction The “gold standard” diagnostic test for assessing in vitro platelet function, light transmission aggregometry (LTA), has limitations to application because of sample requirements. Whole blood or multiple electrode aggregometry (MEA) using the Multiplate® analyzer (Roche Diagnostics) requires smaller blood volumes and less sample manipulation than LTA, making it an attractive clinical testing option. Direct comparisons of MEA with LTA for diagnosis of platelet aggregation abnormalities are few. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Significant differences were observed between agonist doses, suggesting that the device can detect even micromolar changes in ADP and collagen concentrations in whole blood. Low-level aggregation was detected even at minimal agonist concentrations, 1 µM ADP and 1 µg/mL collagen, recommended for clinical application of EIA [35]. These experiments showed that the MICELI aggregometer could be used to evaluate different pathways of platelet activation and provide comprehensive information on platelet function and the effectiveness of antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Significant differences were observed between agonist doses, suggesting that the device can detect even micromolar changes in ADP and collagen concentrations in whole blood. Low-level aggregation was detected even at minimal agonist concentrations, 1 µM ADP and 1 µg/mL collagen, recommended for clinical application of EIA [35]. These experiments showed that the MICELI aggregometer could be used to evaluate different pathways of platelet activation and provide comprehensive information on platelet function and the effectiveness of antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 83%
“…To test the sensitivity of the MICELI device to agonist concentrations in whole blood, platelet aggregation was induced with ADP and collagen. Threshold agonists' concentrations were chosen based on recommendations of the previous studies aimed to validate platelet aggregometry assays for clinical use [35]. The resulting curves showing a linear, dose-dependent increase of platelet aggregation with the increase of agonist concentration are reported in Figure 5.…”
Section: Sensitivity and Precision With Different Aggregation Agonistmentioning
confidence: 99%
“…24 Indeed, a recent report revealed that Multiplate analysis may constitute a less reliable and reproducible tool than light transmission lumi-aggregometry for studying platelet function in pediatric patients. 25 Finally, the bleeding severity was assessed using only one definition (i.e., chest tube output).…”
Section: Discussionmentioning
confidence: 99%
“…An obvious advantage of using whole blood is the negation of need for timeintensive steps of preparing PRP and the ability to perform testing using smaller blood volumes (3 mL). 13 The OPTIMUL assay is another alternative to standard LTA, comprising a 96-well plate into which multiple platelet agonists are added individually into the plate's columns and lyophilized. Subsequent high-throughput aggregometry is performed by adding and mixing (using a specific plate shaker) patient's platelet-poor plasma (PPP) and PRP into the wells, and then recording subsequent changes in absorbance, the surrogate measure of aggregation.…”
Section: Tests Of Platelet Functionmentioning
confidence: 99%